PELAKSANAAN PELAYANAN PUBLIK PADA PT. PEGADAIAN UNIT PELAYANAN CABANG (UPC) KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU - Rendi Sanjaya; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Public Services at PT. Pegadaian Ujung Batu Branch Service Unit (BSU) in Rokan Hulu Regency experienced several problems related to services provided to the community, this can be seen from the problems found, namely, that there are still many administrative officers serving customers not in accordance with Standard Operating Procedures (SOP). This study aims to find out how public services at PT. Pegadaian Ujungpatu Branch Service Unit (BSU) Rokan Hulu Regency. This study uses the concept of Sinambela (2006), which explains that there are 4 theories of public service namely Transparency, Accountability, Conditional, and Participatory. The author uses qualitative research methods by analyzing data descriptively. In collecting research data using interview, observation, and documentation techniques. The results showed that public services at PT. Pegadaian Ujung Batu Branch Service Unit in Rokan Hulu Regency were quite optimal, but there were still problems found, namely the completion time was not in accordance with the SOP, facilities and infrastructure were inadequate, and information get the community will be comfortable in choosing a pawnshop as an alternative funding costs and activities organized by the Pawnshop. Therefore, transparency is expected in the clarity of time in serving people who want to use pawnshops so that the enthusiasm of the community is increasingly increasing to use pawnshops as an alternative funding.Keywords: Service, Public Administration, Standard Operating Procedures.